Influence of the slag content on the chloride and sulfuric acid resistances of alkali-activated fly ash/slag paste. (September 2016) - Lee, N.K.; Lee, H.K.
Abstract: This study aims to investigate the influence of the slag content on the chloride and sulfuric acid resistances of alkali-activated fly ash/slag (AFS) paste. A series of tests were conducted to examine the effects of reaction products and their contents on the chloride and sulfuric acid resistance capabilities. It was shown from the tests that the deterioration of the AFS binder due to a sulfuric acid attack was caused by 1) the corrosion by means of SO4 2− penetration through the surface of the AFS binder, which is associated with permeable voids and a rate of water absorption and 2) the corrosion of the reaction products resulting from the different degrees of resistance to sulfuric attack between the C-(A)-S-H and the N-A-S-H. Variation of the slag content led to differences in the reaction product content of the AFS binder, clearly affecting the chloride-binding capacity and the resistance to chloride penetration.